HYSSOP COMPOSITION DEPENDING ON AGE AND PLANTS DEVELOPMENT PHASES - L. A. Kotyuk (Biotechnologia Acta, 2015)
The aim of the paper is to research biochemical composition of Hyssopus officinalis L. (Lamiaceae) in relation to plant age and phenological growth stage under conditions of Ukrainian Polissya, bin order to determine the optimal harvest dates of the herbal material and its application spheres.